Muscle activity analysis with a smart compression garment - Belbasis, A.; Fuss, F. K.; Sidhu, J. (Procedia Engineering, 2015)
Analysis of muscle exertion while exercising gives insight into an individual's balance, technique and activity performance. Smart Compression Garments (SCG) function as a low-cost material pressure mapping system integrated within consumer compression apparel capable of assessing both muscle use, and limb positioning. The SCG used for testing contained 5 sensors capable of measuring pressure between fabric and skin above key muscle groups of the lower limbs with marker-based video analysis to determine Knee Flexion Angle. The SCG was calibrated through voluntary contractions of target muscles, where surface pressure range and EMG data allowed for the quantification of exertion levels whilst the participant performed leg extension and flexion activities. Each sensor measured a viable range of pressure relative to the exertion level for each muscle group with a strong repeatable nature and correlation to muscle activation load. Additionally, analysis of the muscle loading variation of the quadriceps and hamstrings whilst walking on a treadmill at low speed was shown to match pre-established gait activation behaviour. Results support that a SCG with low-cost integration of piezoresistive materials has considerable promise in determination of muscle loads and potential injury conditions for the purpose of athlete training support.